Analysis of Village Financial Governance in Supporting the Development of Iker Iker Geger Village Cerme District Gresik Regency - Aprilia, Nur Afni; Afiqoh, Nyimas Wardatul (Research Parks Publishers, 2025)
This study aims to determine the description of village financial governance in supporting village development through accountability and transparency of village financial management and community participation in supporting village development. This study focuses on the relationship between village financial management and village development. This type of research is qualitative research based on interviews with 4 informants consisting of the village head, village secretary, and community conducted in Iker Iker Geger Village, Cerme District. The results of the analysis that have been carried out indicate that overall the financial governance of Iker Iker Geger Village has implemented the principles of accountability and transparency well and involved community participation in every stage of development from the planning stage to the implementation of development so that it can support the success of the Iker Iker Geger Village government in implementing development. The Iker Iker Geger Village Government has implemented the principles of accountability and transparency well in village financial management. This is realized through the creation and delivery of a clearly structured Accountability Letter and the provision of information boards in the Village Hall and hamlets. This aims to ensure that village funds are managed accountably and transparently and used according to their intended use to support sustainable development. Community involvement can contribute to the success of development, which is reflected through the delivery of ideas in village deliberation forums and direct supervision of development implementation.